EFFECT OF ORGANOMINERAL AND MINERAL FERTILIZER APPLICATION ON THE CHANGE OF MOBILE NITROGEN IN THE SOIL - Khusanov Sardorbek Olimjonovich; Isakov Fakhriddin Husnidin (European Science Publishing, 2024)
The article highlights the influence of mineral and organomineral fertilizers introduced into the shade in the soil conditions of an ancient irrigated meadow of the Fergana region on the change in nitrogen content in the soil.
Keywords: Soil, soil reserve, nitrogen in the soil, mineral fertilizers, organic fertilizers, tuberous bacteria.